Sistem Pengawasan Pelanggaran P2TL pada PT. PLN (Persero) Berbasis Website - Erfina; Abdul Haq (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2022)
P2TL monitoring system at PT. PLN (Persero) North Makassar Area against electricity theft there are several obstacles faced by the P2TL team, where many people commit fraud to gain profits so that technology for monitoring violations is needed to minimize the occurrence of electricity theft at PLN. The type of research used is descriptive qualitative by using data collection methods namely observation, interviews, and questionnaires. The programming language used is Hypertext Preprocessor (PHP) and MySQL as the database. The system design in this study uses Agile methods and black box testing. This research produces a Website-Based Electric Theft Violation Monitoring Application. Based on the results of the feasibility test of the system, the final results obtained an average of 87.19% of respondents strongly agree with the existence of the system.